Temporal Relationship Between Hyperuricemia and Insulin Resistance and Its Impact on Future Risk of Hypertension. Issue 4 (October 2017) - Han, Tianshu; Lan, Li; Qu, Rongge; Xu, Qian; Jiang, Ruyue; Na, Lixin; Sun, Changhao
Abstract : Although hyperuricemia and insulin resistance significantly correlated, their temporal sequence and how the sequence influence on future risk of hypertension are largely unknown. This study assessed temporal relationship between uric acid and insulin resistance and its impact on future risk of hypertension by examining a longitudinal cohort including 8543 subjects aged 20 to 74 years from China, with an average follow-up of 5.3 years. Measurements of fasting uric acid, as well as fasting and 2-hour serum glucose and insulin, were obtained at baseline and follow-up. Indicators of hepatic and peripheral insulin resistance were calculated. Cross-lagged panel and mediation analysis were used to examine the temporal relationship between uric acid and insulin resistance and its impact on follow-up hypertension. After adjusting for covariates, the cross-lagged path coefficients ( β 1 values) from baseline uric acid to follow-up insulin resistance indices were significantly greater than path coefficients ( β 2 values) from baseline insulin resistance indices to follow-up uric acid ( β 1 =0.110 versus β 2 =0.017; P <0.001, for hepatic insulin resistance; β 1 =−0.208 versus β 2 =−0.021; P <0.001, for peripheral insulin resistance). The path coefficients from baseline uric acid to follow-up insulin resistance indices in the hypertensive group were significantly greater than that in the normotensive group ( P <0.001 for the difference of β 1 values in the 2 groups). Insulin resistance partially mediated the effect of uric acid on subsequent hypertension, and the mediation effect of peripheral insulin resistance was significantly greater than that of hepatic insulin resistance (31.3% versus 13.2%; P <0.001, for the difference of mediation effects). These findings provide evidence that higher uric acid levels probably precede insulin resistance, and peripheral insulin resistance likely plays a more important role in the development of hypertension than hepatic insulin resistance does. Abstract : Supplemental Digital Content is available in the text.